PENGARUH KUALITAS PELAYANAN DAN PENETAPAN HARGA TERHADAP KEPUASAN KONSUMEN PENGGUNA JASA UMROH PADA PT. SILVER SILK TOUR & TRAVEL PEKANBARU - Yusnani "; Endang Sutrisna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research conducted at PT.Silver Silk Tour &Travel Pekanbaru where located in Jl. Aharuddin Nasution No.77 Simpang Tiga Pekanbaru. The problem in this study is the failure of the company’s sales target has not been achieved in the last 5 years and the percentage of sales target achievement has fluctuated, this study aims to determine the influence of service quality and price determination on customer satisfaction Umroh service users at PT. Silver Silk tour & travel Pekanbaru. In this study use quantitative descriptive with SPSS program. The population in this study are consumers who used the umrah service which amount to 4217 persons. The sampling technique chosen is slovin Formula with a sample of 100 respondents.Hypothesis testing uses a simple linear analysis method and multiple linear analysis with results showing that service quality and price determination have a positive and significant effect on customer satisfaction at PT. Silver Silk Tour & Travel Pekanbaru With the calculation of the coefficient of determination (R2 ) service quality on customer satisfaction the value of R square is 0,565 or 56,5% and price determination on customer satisfaction the value of R square is 0,339 or 33,9% and coefficient of determination (R2) service quality and price determination on customer satisfaction the value of R Square is 0.584. This shows that the quality of service and pricing gives an influence of 58.4% on customer satisfaction of Umrah service users at PT. Silver Silk Tour & Travel Pekanbaru, while the remaining 41.6% is influenced by other variables that are not examined in this study.Key words: Service quality, price determination, Customer satisfaction